The emergence of agriculture a global view - Denham, Tim; White, Peter 1937 Oct. 8- (One world archaeology readers, 2007)
The Emergence of Agriculture' is a compendium of key papers by leaders in the field in different parts of the world. Each is supplemented by a review of developments in the field since its publication.